A Defense of Shepherd’s Account of Cause and Effect as Synchronous - David Landy (Journal of Modern Philosophy, 2020)
Lady Mary Shepherd holds that the relation of cause and effect consists of the combination of two objects (the causes) to create a third object (the effect). She also holds that this account implies that causes are synchronous with their effects. There is a single instant in which the objects that are causes combine to create the object which is their effect. Hume argues that cause and effect cannot be synchronous because if they were then the entire chain of successive causes and effects would all collapse into a single moment, and succession would not be possible. I argue that Shepherd has a ready, although implicit response, to Hume’s argument. Since causation is combination on Shepherd’s view, she is free to hold that there are times in between those instants in which combinations occur, during which times other, non-combinatory changes (such as changes in the location of objects) occur, which changes account for succession.